Human UTP14a promotes colorectal cancer progression by forming a positive regulation loop with c-Myc. (January 2019) - Zhang, Jingyi; Ren, Pengwei; Xu, Da; Liu, Xiaofeng; Liu, Zhenzhen; Zhang, Chunfeng; Li, Yuan; Wang, Lijun; Du, Xiaojuan; Xing, Baocai
Abstract: Nucleolar protein hUTP14a is required for 18S rRNA processing and promotes p53 degradation. Here, we report that hUTP14a stabilizes c-Myc in colorectal cancer (CRC) progression. Firstly, nucleolar hUTP14a is upregulated in human CRC tissues. Mass spectrometry analysis identified c-Myc and its deubiquitinase ubiquitin-specific protease 36 (USP36) in the hUTP14a-specific complex. Importantly, hUTP14a interacts with c-Myc and protects c-Myc from ubiquitination and degradation in a USP36-dependent way. We further demonstrate that hUTP14a forms a complex with USP36/Fbw7γ to inhibit Fbw7γ-mediated c-Myc degradation. Ectopic expression of Flag-hUTP14a enriches c-Myc in the nucleolus, indicating hUTP14a stabilizes c-Myc in the nucleolus. Interestingly, c-Myc activates transcription of hUTP14a. Knockdown of hUTP14a by short hairpin RNA inhibits tumor growth and decreases c-Myc levels in mouse xenografts. Significantly, nucleolar hUTP14a and c-Myc are co-upregulated in human CRC tissues, and this co-upregulation indicates poor prognosis of CRC patients. Thus, disruption of hUTP14a-c-Myc regulation may provide a potential therapeutic strategy for a subset of CRC patients. Highlights: Expression of nucleolar hUTP14a is significantly upregulated in CRC tissues. hUTP14a protects c-Myc from Fbw7γ-mediated degradation by binding to Fbw7γ/USP36. hUTP14a is a downstream gene of c-Myc. Upregulated nucleolar hUTP14a and c-Myc indicates poor prognosis of CRC patients.